Identification of Strategic Human Capital Components and Examination of Its Impact on Innovative Work Behaviors with Job Embeddedness Moderation - ALI Al-Luhaibi, Hasan Hadi; Eslami, Ghasem; Rahimnia , Fariborz; Khorakian, Ali Reza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aimed to identify the components of strategic human capital and its impact on employees’ innovative work behaviors with the moderating role of job embeddedness in Karbala municipal offices. Methodology: The present research adopted a mixed-method (qualitative and quantitative) approach, gathering data through systematic review, Delphi method, and questionnaires. Findings: In the systematic review section, 27 primary indicators of strategic human capital were identified, from which, following Delphi surveys and exploratory factor analysis, three main components were extracted: "value creation and strategic competitiveness," "agility and strategic adaptability," and "alignment and strategic participation." In the quantitative phase, using structural equation modeling, the positive impact of strategic human capital on innovative work behaviors was confirmed, and the moderating role of job embeddedness in this relationship was found to be significant. Conclusion: The results indicate that strategic human capital effectively enhances innovative behaviors and creates a conducive environment for improving organizational performance. By identifying the components of strategic human capital and examining its effective mechanisms, this study contributes to filling gaps in the research literature and provides practical suggestions for enhancing human resource management.